Universal Minimum Old Age Pensions : Impact on Poverty and Fiscal Cost in 18 Latin American Countries - Dethier, Jean-Jacques; Pestieau, Pierre; Ali, Rabia (2012)
Alleviating poverty for the elderly requires a different approach from other age groups, and a minimum pension is likely to be the only viable option. This paper examines the impact on old age poverty and the fiscal cost of universal minimum old age pensions in 18 Latin American countries using recent household survey data. First the authors measure old age poverty rates for these countries. Then they discuss the design of minimum pensions schemes -- means-tested or not -- as well as the disincentives they introduce for the economic and social behavior of households including labor supply, saving and family solidarity. Finally, the authors use household survey data to simulate the fiscal cost and the impact on poverty rates of alternative minimum pension schemes in the 18 countries. They show that a universal minimum pension would substantially reduce poverty among the elderly (except in Argentina, Brazil, Chile and Uruguay where minimum pension systems already exist and poverty rates are low). Such schemes have much to be commended in terms of incentives, spillover effects and administrative simplicity, but they have a high fiscal cost. The latter is a function of the age at which benefits are awarded, the prevailing longevity, the generosity of benefits, the efficacy of means testing, and the fiscal capacity of the country.